The Russian-Ukrainian Crisis and Behind, Energy Policy in the Mirror of Eurasian Game of Geopolitics - Péter Bertalan; András Nagy (DETUROPE)
The Russian-Ukrainian crisis is one of the most important issues of the beginning of the 21st century, from regional and global aspects as well. This paper analyses the crisis from geopolitical aspects, and tries to concentrate on the reasons behind the events and the global perspectives. The study reveals why the Ukrainian question is in the focus of Russian interest, and what led to the crisis. Concerning geopolitics, starting from the point of view of Sir Halford John Mackinder, placing the theory of the Heartland to the 21st century, the study gives a complete picture about the situation of the Eurasian chessboard in terms of Ukraine and Russia. The authors attempt to provide comprehensive analysis of the crisis, keeping in mind the spheres of interests of Russia, Ukraine, the U.S. and the European Union.